Gnrh mRNA expression in the brain of cooperatively breeding female Damaraland mole-rats. Issue 4 (April 2017) - Voigt, Cornelia; Bennett, Nigel C
Abstract : The Damaraland mole-rat ( Fukomys damarensis ) is a eusocial, subterranean rodent, in which breeding is limited to a single reproductive pair within each colony. Non-reproductive females, while in the confines of the colony, exhibit socially induced infertility. Anovulation is thought to be caused by a disruption in the normal gonadotropin-releasing hormone (GNRH) secretion from the hypothalamus. To assess whether social suppression is associated with altered Gnrh mRNA expression in the brain, we investigated the distribution and gene expression levels by means of in situ hybridization in female breeders and non-breeders from field captured colonies of the Damaraland mole-rat. We found expression of Gnrh mRNA as a loose network in several forebrain areas of female Damaraland mole-rats with the majority of labelling in the preoptic and anterior hypothalamus. The distribution matched previous findings using immunocytochemistry in this and other social mole-rat species. Quantification of the hybridisation signal revealed no difference between breeding and non-breeding females in the average optical density of the hybridization signal and the size of the total area covered by Gnrh mRNA. However, analysis along the rostro-caudal axis revealed significantly elevated Gnrh mRNA expression in the rostral preoptic region of breeders compared to non-breeders, whereas the latter had increased Gnrh mRNA expression at the caudal level of the anterior hypothalamus. This study indicates that social suppression affects the expression of Gnrh mRNA in female Damaraland mole-rats. Furthermore, differential regulation occurs within different neuron subpopulations.